PRGF as adjunct to DBB in maxillary sinus floor augmentation: histological results of a pilot split-mouth study - Leonidas Batas; Lazaros Tsalikis; Andreas Stavropoulos (SpringerOpen, 2019)
Abstract Background Various technologies of autologous blood concentrates are currently evaluated for their potential to enhance bone formation. Aim To report on the histological outcome of maxillary sinus floor augmentation (MSFA) with deproteinized bovine bone (DBB) in combination with chair-side prepared autologous platelet-rich growth factor (PRGF), in comparison to that with DBB alone. Materials and methods Six partially edentulous patients with ≤ 3-mm residual bone height bilaterally in the posterior maxilla were subjected to MSFA with the lateral window technique, using DBB in combination with PRGF (PRGF System1 Vitoria, Spain) on one side or DBB alone on the contralateral side. Cylindrical biopsies from the augmented sinuses were collected during implant installation, ca. 6 months post-MSFA, and subjected to non-decalcified histological and histomorphometric evaluation. Results The collected biopsies varied in length (range 3.5-9.9 mm); consequently, the portion of the biopsy representing augmented tissues also varied (range 2.3-14.6 mm2). New bone formation with a trabecular appearance and numerous DBB particles in contact with the new bone or with loose connective tissue were observed. No differences in the relative volumes of bone formation were found in sinuses augmented with DBB + PRGF or DBB alone 6 months after MSFA (35.6 ± 8.26 mm and 37.8 ± 3.15 mm, respectively). Conclusion and clinical implications In conclusion, based on these preliminary results, PRGF as adjunct to DBB for MSFA, except from improved handling during the operation, does not appear to enhance nor interfere with bone formation inside the human sinus 6 months after MSFA, compared with the use of DBB alone.